Severe COVID-19 induces prolonged elevation of the acute-phase protein pentraxin 3 - Kratzer, Bernhard; Stieger, Robert B.; Durmus, Seyma; Trapin, Doris; Gattinger, Pia; Ettel, Paul; Sehgal, Al Nasar Ahmed; Borochova, Kristina; Dorofeeva, Yulia; Tulaeva, Inna; Grabmeier-Pfistershammer, Katharina; Tauber, Peter A.; et al. (Frontiers in Immunology, 2025)
IntroductionDuring the acute-phase of COVID-19, elevated levels of several acute-phase proteins, such as C-reactive protein (CRP), mannose-binding lectin (MBL), pentraxin 3 (PTX-3), serum amyloid A (SAA) and surfactant protein D (SP-D), are associated with severe to fatal clinical outcomes. Typically, these markers return to baseline within days after resolution of the acute infection.MethodsIn this study, we assessed the plasma levels of these proteins in a well-defined cohort of 141 COVID-19 convalescent patients 10 weeks after infection and compared them to 98 non-infected controls. In addition, we performed genetic analyses in a subgroup of patients and related the findings with structural equation modelling to disease severity. ResultsIn contrast to other acute-phase proteins, PTX-3 levels were significantly higher in severe COVID-19 convalescent patients than in the control group. Furthermore, a higher proportion of patients with severe COVID-19 exhibited PTX-3 levels above 5000 pg/ml even 10 months post-infection, compared to those with mild disease. To explore potential genetic influences, a genetic analysis was performed on all severely affected patients (n=36) and on an age- and sex-matched subset of mild COVID-19 patients (n=38). Results revealed a significantly higher frequency (p<0.0001) of the homozygous wildtype genotype of the PTX-3 SNP rs971145291 in severe (15 out of 36) versus mild (1 out of 38) COVID-19 patients. Using structural equation modelling, the association of this PTX-3 genotype and disease severity was shown to be mediated by elevated PTX-3 levels, with no contribution from other analyzed (clinical) confounders. DiscussionIn summary, severe COVID-19 patients show high PTX-3 serum levels which may be influenced by genetic predisposition, specifically the absence of the rs971145291 SNP variant. PTX-3 may thus serve both as a biomarker for tissue damage and/or long-term immune activation and eventually post-COVID-19 complications.